From research to practice: Adapting agriculture to climate today for tomorrow in Ethiopia - Grossi, Amanda; Dinku, Tufa (Frontiers in Climate, 2022)
The Adapting Agriculture to Climate Today for Tomorrow (ACToday) approach of the International Research Institute for Climate and Society (IRI), Columbia University, USA, aims to develop climate service solutions through enhancement of the availability and effectiveness of climate information in national policy, planning, management, and other decision-making processes in countries that are particularly dependent on agriculture and vulnerable to the effects of climate variability and change. It targets improved food security, nutrition, environmental sustainability and economic outcomes in these countries by promoting the use of climate information and services to manage current climate risks, while laying the foundation for adaptation to future climatic conditions. In this paper, we share experiences from the implementation of the ACToday project and approach in Ethiopia, outlining its accomplishments and challenges. In doing so, we characterize best practices and pitfalls to avoid to ensure climate knowledge and information truly meet the needs of climate-informed decision making and climate-smart policy and planning. We also outline pragmatic guidance to ensure activities designed to evolve climate research into services are done so appropriately, responsibly, and sustainably to bridge the gap between those who produce climate information and those who ultimately use it.